Teaching Learning Process Of Writing Skill At English Department Of Muhammadiyah University Of Surakarta: A Micro Ethnography - Setyaningsih, Agustina (2012)
This research is aimed at describing teaching learning process of writing skill at the fourth semester English Department of Muhammadiyah University of Surakarta. It is conducted to describe (1.) learning objective, (2.) syllabus, (3.) material, (4.) methods of teaching writing, (5.) classroom procedure and activity, (6.) teacher role and learner role, (7.) media used in teaching writing, (8.) the strength and weaknesses of teaching learning process of writing skill at English Department of Muhammadiyah University of Surakarta. Type of the research is descriptive qualitative research; the writer uses one of them that is micro ethnography. In this research the data derived from event, informant and document. There are three techniques in collecting data namely; observation, interview and document. The researcher used reduction of the data, display the data, conclusion and verification in analyzing data. The data are achieved from information related to the process of teaching writing IV in the form of field note, interview scripts and document. The results of the study show that: 1.) the learning objective is to help the students preparing conduct the research paper, 2.) the type of the syllabus of writing IV is Task Based Syllabus, 3.) the material in teaching writing IV, the teacher used Writing for Academic English and The Handbook of Composition, 4.) the method used in teaching writing IV is GTM, Discussion Methods and Direct Methods, 5.) classroom procedure and activity is pre activity, main activity and post activity. 6.) the roles of the teacher are as manager, as instructor, as facilitator, as evaluator and as counselor and roles of the learner are as a listener and speaker and as a performer. 7.) the media used in teaching learning of writing skill at English Department of Muhammadiyah University of Surakarta is various, such as computer or laptop to displaying the material into LCD, textbook, realia, etc. 8.) the strength of the methods used is students enjoy the writing subject in the classroom. Besides the strength, there are weaknesses of teaching writing, such as there are many students who do not understand the target language because the teacher used native language more frequently than target language, in addition the teacher also needs much time to explain the material in the classroom.